Completion of CVRP model using sweep algorithm and guided local search algorithm for route optimization (case study: PT. Sumber Berkah Farmasi) - Fajrie Novardhan Winadi (Unnes Journal of Mathematics, 2023)
Optimizing distribution costs can be done in various ways, one of these methods is determining the distribution route to be the optimal route. The optimal route has many indicators, one of these indicators is having the shortest route or the shortest distance traveled. Problems with optimizing routes and distribution costs occur at PT Sumber Berkah Farmasi. PT SBF is a sub-distributor of medicines to pharmacies in Central Java. The purpose of this research is to optimize distribution routes of PT SBF. Route optimization is carried out using the Sweep Algorithm which is calculated manually, followed by a comparison with the use of the Guided Local Search Algorithm from the Google OR-Tools library. The application of this algorithm requires data obtained from interviews, observations, and calculations using Google Maps to determine the distances between pharmacies. From the results of this study it can be concluded that the Guided Local Search Algorithm can generate route savings of 82 km or 23% and distribution cost savings of Rp. 27,306 or 26% of the route and initial distribution costs by the company. Meanwhile, the Sweep Algorithm resulted in route savings of 20 km or 5.6% and cost savings of Rp. 6,660 or 5,7% of the route and initial distribution costs by the company. Thus it can be concluded that the use of the Guided Local Search Algorithm can be used as an alternative in finding the optimal route for PT. Sumber Berkah Farmasi.